WARISAN KOMUNIKASI BUDAYA KUNO RELEVANKAH BAGI GENERASI KINI ? - Gunadi, YS (WACANA, Jurnal Ilmiah Ilmu Komunikasi, 2007)
Since long time years ago our ancient has hight cultural communication values who has describe in the old lontar or papirus books, the destination to teach one generation to generation. Beyon mt expectations, this article communicationan has enjoyed a very hearty and warm reciept from both old and modern generations di indonesia. Several friends among modern families, who are about toadhere the old teach faith, have given up tehir intention, and remain modern men.The modern mens now have quetioner, what about old guiden life has pratice arround attentions with morm or ethicaly. And be the Tembang Pangkur and Dandanggula give us for the guideline in our good life.Donât forgot with old message who directed by our ancient as message from writers as Mangkunegoro (rex of Surakarta kingdom), Gesang (the composed Caping Gunung Song), and no name anathers. So, the of all sentenses description in its manuscript for you to become wisdom and a good communicatipons in your life.